Estratégia como prática social em redes interorganizacionais: um estudo na perspectiva da teoria ator-rede - Morais, César Augusto Tureta de (2007)
Interorganizational networks have been focused from diverse studies that analyze them through distinct points of view. However, in dealing with the thematic of "networks strategy", in general it has a predominance of macro level perspectives, whose ontological and epistemological orientation are based on the modern thought perspectives. Aiming to apprehend the strategic process in an interorganizational network of small and medium size enterprise, we adopt the Strategy as Social Practice perspective, to analyze in the practical activities of the network, how strategies emerge and spread among the actors. This perspective allows getting simultaneously the common and divergent interests that can occur in the extent of such arrangement. Thus, this dissertation adopted Actor-Network Theory as methodological pathway to provide the possibility to investigate the actors-networks in a local and specific context, composed by human and non-human actors. In this way one can (re)constitute the strategic practices in the relations among several actants. The research unfolds on the basis of qualitative-description of a case study, without assuming a priori what it is strategy. The data allowed identify some interaction moments (have lunch, meeting and coffee break) in which the strategists translate theirs interests. Through of depth interviews, non-participant observation and documentary analysis, we verified the existence of four principal strategic subjects (Negotiations/Purchases, Price, Brand/Franchising and Credit Card) as the main strategic orientation of the actors in the network. We still observed the importance of the non-human elements in the strategic process, as well as its active participation, as agents, in strategizing. We conclude that strategies emerge and spread out through relations among human and non-human elements in the social practices, and its development is pointed out by tension among several and contradictory interests of actors. In such a way, there isn´t anything certain and irreversible in the strategizing process of the investigated network. Therefore, the strategies stabilize, temporarily acquiring new forms at the moment another elements enter into the actor-networks which generate such strategies.